Analysis of flow in pulse combustor tailpipe - Mohd. Radzi, Abdul Qoiyum (Penerbit UTM, 2008)
Pulse combustion is known to have the higher combustion efficiency compared to conventional steady type burner in heating application (Putnam, 1971). However, there are many parameters need for scientific study in designing this kind of combustor. This study intends to model the pulse combustion in order to determine important characteristics that govern the performance of the pulse combustor. The important parameters identified in this study namely frequency, pressure oscillation and pulsating flow inside tailpipe. This study will be useful for predicting the capability of pulse combustor especially in heating application.